Annual changes in energy quality and quality of life: A cross-national study of 29 OECD and 37 non-OECD countries - Bowen Liu; Jun Matsushima (Energy Reports, 2019)
Since the efficiency of obtaining energy is decreasing, it is important to determine how the degradation in energy quality will influence society. Despite the rising importance of net energy, few quantitative studies have been conducted on the relationship between energy quality and quality of life (QoL). Energy return on investment on a society scale at a national level (EROIsoc) is used as an indicator of energy quality, energy consumption (EC) per capita is used to represent energy quantity, and gross domestic product (GDP) per capita is used as an economic factor. Eight indices are used for QoL. Simple linear regression analysis is used to discuss the correlation coefficients between the three indicators (EROIsoc, GDP per capita, and EC per capita) and eight QoL indices for 29 OECD and 37 non-OECD countries, and their annual changes over the 25 years from 1990 to 2015. We demonstrate that the relationship between the three indicators and eight QoL indices changes annually and differs between OECD and non-OECD countries. We also demonstrate that although GDP per capita is the most influential factor among the three indicators for the Human Development Index (HDI), which is one of the best-known composite indices of well-being, the importance of GDP per capita for non-OECD countries has declined, especially in times of increasing energy prices, while the importance of EROIsocfor OECD countries has increased. Keywords: Energy return on investment (EROI), Quality of life (QoL) sep Energy consumption, Gross domestic product (GDP), Regression analysis, Energy price